Politik Hukum Terhadap Kedudukan Dan Kewenangan Komisi Pemberantasan Korupsi Pasca Berlakunya Undang-Undang Nomor 19 Tahun 2019 - Ilham Hidayat Azis; Anshori Ilyas; Zulkifli Aspan (Jurnal Sosio Sains, 2022)
The research objectives to analyze the Authority of the Corruption Eradication Commission after the enactment of Law No. 19 of 2019. This research was conducted using doctrinal legal research methods or normative legal research. The results of the study show that: 1) The authority of the Corruption Eradication Commission (KPK) after the promulgation of Law no. 19 of 2019 concerning the Second Amendment to Law No. 30 of 2002 concerning the Corruption Eradication Commission, with the stipulation of a Supervisory Board within the KPK Institution which has considerable authority, namely supervisory authority and also added authority to carry out the KPK's authority. The position of the Corruption Eradication Commission (KPK) after the enactment of Law no. 19 of 2019 concerning the Second Amendment to Law No. 30 of 2002 concerning the Commission for the Eradication of Criminal Acts of Corruption, he emphasized in Article 3 that the KPK Institution is a State Institution within the executive clump, and also the addition of a Supervisory Board within the KPK Institution whose members are appointed directly by the President and can also be dismissed during their term of office by the President The Republic of Indonesia, with considerable authority, namely in terms of wiretapping, searches and/or confiscations carried out by the KPK must first obtain permission from the Supervisory Board. Tujaun penelitian menganalisis Kewenangan Komisi Pemberantasan Korupsi pasca pemberlakuan UU No 19 Tahun 2019. Penelitian ini dilakukan dengan menggunakan metode penelitian hukum doktrinal atau penelitian hukum normative (normative legal research). Hasil penelitian menunjukan bahwa: 1) Kewenangan Komisi Pemberantasan Korupsi (KPK) setelah diundangkannya UU No. 19 Tahun 2019 Tentang Perubahan Kedua Atas UU No. 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi, dengan diaturnya Dewan Pengawas Dalam Lembaga KPK yang memiliki kewenangan yang cukup besar yaitu kewenangan pengawasan dan juga ditambahkannya kewenangan dalam melaksanakan kewenangan KPK. Kedudukan Komisi pemberantasan Tindak pidana Korupsi (KPK) pasca berlakunya UU No. 19 Tahun 2019 Tentang Perubahan Kedua Atas UU No. 30 Tahun 2002 Tentang Komisi Pemberantasan tindak Pidana Korupsi, dengan ditegaskannya dalam Pasal 3 bahwa Lembaga KPK adalah Lembaga Negara yang ada dalam rumpun eksekutif, dan juga ditambahkannya Dewan Pengawas Dalam Lembaga KPK yang anggotanya diangkat langsung oleh Presiden dan juga dapat diberhentikan dalam masa jabtannya oleh Presiden Republik Indonesia, dengan kewenangan yang cukup besar yaitu dalam hal penyadapan, Pengeledahan dan/atau Penyitaan yang dilakukan oleh KPK harus terlebih deahulu dapat izin dari Dewan Pengawas